TECHNO-ECONOMIC STUDY OF CO2 UTILIZATION FROM TAIL GAS STEAM REFORMING UNIT INTO METHANOL AT OIL REFINERIES IN INDONESIA - Priyanto, Ragil; Wahid, Abdul (Konsorsium Cendekiawan Indonesia, 2024)
The downstream oil and gas sector contributes significantly to CO2 emissions, particularly from steam methane reforming (SMR), which produces 4.33 tCO2e/kbbl of crude oil processed. This study investigates the technical and economic feasibility of utilizing CO2 from SMR tail gas to produce methanol. The process simulation was conducted using Aspen HYSYS v12, modeling the methanol synthesis process through the hydrogenation of CO2 with hydrogen (H2) sourced from the Naphtha Reforming Unit. Results from the simulation indicate an optimal methanol yield of 81.16% at 235°C and 50 bar, producing 70 tons/hour (612 KTA) of methanol with a purity of 99.85% wt. The economic analysis reveals an IRR of 8.04%, an NPV of -26.5 million USD, and a pay-out time (POT) of 22 years, showing that the project is not yet economically feasible under current conditions. Sensitivity analysis highlights that methanol selling price and production capacity are the most critical factors impacting the project's viability, where a 20% increase in methanol price or production capacity could significantly improve IRR above the hurdle rate of 10.83%. This study provides insight into the potential of CO2 utilization for methanol production, contributing to emission reduction and product diversification in refineries. Further optimization of feedstock costs and integration with downstream products like MTBE could enhance economic feasibility.